LCTL Is a Prognostic Biomarker and Correlates With Stromal and Immune Infiltration in Gliomas - Su, Jun (Front Oncol, 2019)
Immune evasion in glioma strongly correlates with clinical outcomes; however, the molecular mechanisms driving the maintenance of immunosuppression remain largely unknown. Recently studies demonstrate that Klothos are aberrantly expressed in several cancers and are potential therapeutic targets in cancers. However, their roles are still unclear in glioma. Here, we show that LCTL is highly expressed in gliomas and that its expression is regulated by DNA methylation status at the promoter. LCTL expression is also found to be significantly associated with high tumor aggressiveness and poor outcomes for glioma patients. Mechanistically, results suggested that LCTL might play an important immunosuppressive role by recruiting immunosuppressive cells and regulating tumor-associated macrophages polarization, T cell exhaustion, and epithelial–mesenchymal transition through FGF signaling in glioma. Our results establish LCTL as a key biomarker for prognosis that could be considered a potential epigenetic and immunotherapeutic target for treatment.